2020
DOI: 10.3390/jof6040342
|View full text |Cite
|
Sign up to set email alerts
|

Low Efficacy of Isaria fumosorosea against Box Tree Moth Cydalima perspectalis: Are Host Plant Phytochemicals Involved in Herbivore Defence against Fungal Pathogens?

Abstract: Buxus sp. is an important native and ornamental tree in Europe threatened by a serious invasive pest Cydalima perspectalis. The larvae of this moth are able to defoliate box trees and cause their death. The development of novel biopesticides targeting this pest might help protect Buxus trees grown wildly or in city parks. Laboratory experiments were conducted to assess the efficacy of entomopathogenic fungus Isaria fumosorosea strain CCM 8367 against C. perspectalis. The last-instar larvae of the box tree moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Abnormal changes in emerged adults having crippled wings was observed for the first time in E. amabilis when treated with I. fumosorosea strain, which was a significant finding. As a result, the deformed adults fail to perform normal flight behavior and mating, which was earlier reported in Cydalima perspectalis and Spodoptera litura (Zemek et al 2020). The egg mortality was found the highest (40.00%) at 1 × 10 7 spore/ml upon infection, which was significantly lower as compare to other stages of E. amabilis, which proposed that the egg stage was the most resistant stage to fungal infections (Mochi et al 2009).…”
Section: Discussionmentioning
confidence: 56%
“…Abnormal changes in emerged adults having crippled wings was observed for the first time in E. amabilis when treated with I. fumosorosea strain, which was a significant finding. As a result, the deformed adults fail to perform normal flight behavior and mating, which was earlier reported in Cydalima perspectalis and Spodoptera litura (Zemek et al 2020). The egg mortality was found the highest (40.00%) at 1 × 10 7 spore/ml upon infection, which was significantly lower as compare to other stages of E. amabilis, which proposed that the egg stage was the most resistant stage to fungal infections (Mochi et al 2009).…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, several studies have documented that the persistence of EPF spores on plants is limited by many factors such as temperature, rainfall, low humidity, solar radiation, plant chemistry, host plant genotype, fungal strain, etc. [58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Reference strain CCM 8367 of I. fumosorosea caused 40% mortality which was slightly higher compared to the two other I. fumosorosea strains tested. This strain was reported to be a promising biocontrol agent against several insect pests (Hussein et al 2013(Hussein et al , 2016Prenerová et al 2013) although recent findings demonstrated that some pests might be resistant to infection (Zemek et al 2020). The strain also turned out to be virulent against T. urticae (Zemek et al 2016).…”
Section: Discussionmentioning
confidence: 99%